2018
DOI: 10.5210/ojphi.v10i1.8576
|View full text |Cite
|
Sign up to set email alerts
|

Developing policy to support novel Caribbean Tourism and Health surveillance program

Abstract: ObjectiveThe Regional Tourism and Health program (THP) is a novel program, comprising of a tourism surveillance system, training, standards and multisectoral partnerships. The objective was to develop regional mandate and policy to support this new program and its non-traditional surveillance system.IntroductionIn January 2016, the Caribbean Public Health Agency (CARPHA), serving 24 Member States(MS), began executing a regional Tourism and Health program (THP), recognizing that the health of Caribbean economie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is likely that the Norovirus quickly spread from the employees to the guests. Most of the foodborne illnesses go unreported in the Caribbean due to lack of surveillance systems (30), an issue that led to the development of the Tourism and Health Program in 2016, that was aimed at improving surveillance with tourism and health threats among Caribbean countries (27). In a study to evaluate the food safety knowledge of foodservice workers at a university campus in the Caribbean (Trinidad and Tobago), it was found that food handlers had inadequate knowledge about time temperature control of food, cleaning and sanitation of food contact surfaces, and could not identify symptoms of a sick food handler that needed to be excluded from working with food (58).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the Norovirus quickly spread from the employees to the guests. Most of the foodborne illnesses go unreported in the Caribbean due to lack of surveillance systems (30), an issue that led to the development of the Tourism and Health Program in 2016, that was aimed at improving surveillance with tourism and health threats among Caribbean countries (27). In a study to evaluate the food safety knowledge of foodservice workers at a university campus in the Caribbean (Trinidad and Tobago), it was found that food handlers had inadequate knowledge about time temperature control of food, cleaning and sanitation of food contact surfaces, and could not identify symptoms of a sick food handler that needed to be excluded from working with food (58).…”
Section: Introductionmentioning
confidence: 99%